Comparative study with or without application of enhanced recovery after surgery protocols in patients undergoing elective cesarean section - Pravina, Pammy; Tewary, Khushbu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Concept of enhanced recovery after surgery (ERAS) has been applied in various surgical branches. Evidence regarding the necessary components of ERAS for obstetric population is limited. Therefore, objective of this study was to test the application of ERAS in patients undergoing elective caesarean section on the post-operative recovery process. Methods: The study was conducted in the Department of Obstetrics and Gynecology, NMCH, Patna from January 2014 to December 2014. A total of 100 patients (n=100) undergoing elective caesarean section were included in the study. Cases were allocated into two groups a) Study group included 60 patients (n=60) and ERAS protocol was followed b) Control group included 40 patients (n=40) and standard post-operative care protocol was followed. Two groups were compared with respect to recovery parameters, post-operative complications and satisfaction rates. Results: More patients in the ERAS group were discharged on post-operative day 4 than the standard postoperative care group (90% vs 12.5%, p<0.0001). More patient in the ERAS group were significantly satisfied with the protocol compared to standard post-operative care (77% vs 70%, p<0.04). Approximately 77 percent of the patients in the ERAS group rated the satisfication score between 8-10 compared to 70 percent of the patients in control group (p<0.04). There was no difference between two groups with respect to recatheterization rate, readmission rate and post-discharge complaints. Conclusions: In this study with application of ERAS protocol, we reported reduced hospital stay which may reduce financial burden of patients and healthcare facilities.